Theological Meaning off Malapeh Kawua Padi Tradition in Koto Community of Pasaman Regency - Erna Permata Sari; Muallim Lubis (NALAR, 2026)
Local traditions are an important part of community life, serving not only as cultural practices but also embodying profound religious values. Amid the tide of globalization, the meanings of various traditions are shifting, making scientific research necessary to understand the spiritual values they contain. One tradition that is still preserved is the malapeh kawua padi among the Koto people in Jorong Garagah, Nagari Simpang, Pasaman Regency, which is performed as an expression of gratitude to Allah is Most Holy and Most High for the harvest. This study aims to examine the theological meaning within this tradition. The method used is a qualitative approach with an ethnographic research design, analyzed using contextual theology theory. Data were collected through observation, interviews, and documentation of the community involved in the practice of the tradition. The results of the study indicate that the “malapeh kawua padi” is not merely a customary practice but also contains profound theological significance. Elements such as prayer, vows, animal sacrifice, and communal eating reflect gratitude and humanity’s dependence on Allah is Most Holy and Most High. Through a contextual theology approach, it can be understood that the values of faith among the Koto people are integrated into social and cultural practices, making this tradition a form of religious expression in daily life.